2020
DOI: 10.1108/ijebr-07-2019-0457
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial orientation and firm performance in Italian firms

Abstract: PurposeConsidering that context is important and relying on a contingency perspective, the purpose of the study is to analyze the relationship between an entrepreneurial orientation (EO) and firm performance in one of the world's oldest economies: Italy. The contingency perspective relies on competitive strategy as a moderating variable.Design/methodology/approachUsing a mix of primary and secondary data sources, relationships are explored in a sample of 229 Italian for-profit firms. Moderated regression analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
106
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(117 citation statements)
references
References 81 publications
(126 reference statements)
7
106
0
4
Order By: Relevance
“…The EO-performance link is still recognized as a high relevant topic, as many recent papers are still focusing on such link. Galbreath et al (2020) analyzed this relationship and firm performance in a specific context, the Italian one, which is considered as one of the oldest economies. The authors confirm the positive association between EO and performance, adding that competitive strategy operates as a moderator: a low-cost strategy negatively influences the relationship, while a differentiation strategy positively influences the relationship (Galbreath et al, 2020).…”
Section: Eo-performance Relationshipmentioning
confidence: 99%
“…The EO-performance link is still recognized as a high relevant topic, as many recent papers are still focusing on such link. Galbreath et al (2020) analyzed this relationship and firm performance in a specific context, the Italian one, which is considered as one of the oldest economies. The authors confirm the positive association between EO and performance, adding that competitive strategy operates as a moderator: a low-cost strategy negatively influences the relationship, while a differentiation strategy positively influences the relationship (Galbreath et al, 2020).…”
Section: Eo-performance Relationshipmentioning
confidence: 99%
“…Tradicionalmente, a OE vem sendo investigada e instrumentalizada no nível organizacional, pois o proprietário/gestor observa e repassa para suas firmas (Covin et al, 2020;Wales, Gupta, & Mousa, 2013) posturas que capazes de influenciar o processo de tomada de decisão e, consequentemente, o desempenho organizacional (Covin & Slevin, 1989;Galbreath, Lucianetti, Thomas, & Tisch, 2020;Lyon, Lumpkin, & Dess, 2000).…”
Section: Introductionunclassified
“…Dentre os estudos que analisam a relação entre a OE e o desempenho, há o consenso de que os impactos mudam de acordo com as variáveis, isto é, conforme o setor de atuação, o tipo de empresa, entre outros fatores (Covin & Wales, 2019). Nesse ínterim, amostras de diferentes países podem apresentar particularidades nos achados, tendo em vista que as investigações normalmente se concentram nos Estados Unidos e na Europa Ocidental (Galbreath et al, 2020;Rauch, Wiklund, Lumpkin, & Frese, 2009). Isso indica que, muitas das vezes, as conclusões não podem ser generalizadasfato que justifica a elaboração de pesquisas em novos contextos (Basco, Hernández-Perlines, & Rodríguez-Garcia, 2019;Martens, Lacerda, Belfort, & Freitas, 2016;Shu, De Clercq, Zhou, & Liu, 2019).…”
Section: Introductionunclassified
“…However, none of these studies dared to investigate the nature of strategy formulation amongst SMEs and the effect thereof on their financial performance in Zimbabwe. Galbreath et al (2020) observed that generalising results from other contexts could be misleading because countries have different cultures and idiosyncrasies and firms respond differently to different contexts. In this regard, Shu et al (2019) called for scholars to research different and new contexts.…”
Section: Introductionmentioning
confidence: 99%